Using Cybernetics for Early Detection of Instructional Problems in the Chilean Educational System - Martín Schaffernicht; Patricio Madariaga Araya (Universidad Autónoma de Baja California, 2002)
We have posulated that in order to avoid the loss of opportunities in education, it is desirable and feasible to develop a detection system for problems during the teaching processes. We have based this on two disciplines. From cybernetics we took the idea of the logically autoreferential system which adjusts itself automatically and is analogous to Beer's viable system model. From theories of learning, we presented a learning-action focus that distinguishes various hierarchical cycles. We distinguished two time horizons: one, for courses that managed the improvements between two versions of themselves; the other, concerned with improving the processes while the course is being carried out. At this level, we differentiated between the student, the group of students, and the teacher, as possible sources of imbalances. The general process of three cycles proposed indicators for the early detection of problems; furthermore, it has shown an capability for self-adjustment, and is under further investigation. The experience has been developed in the context of computer-training associated with the ENLACES Network which the University of Talca offers to teachers of middle schools and high schools, as well as subsidized private schools in the Maule Region of Chile.